2016
DOI: 10.1007/978-3-319-32859-1_49
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Likelihood Estimates for Gaussian Mixtures Are Transcendental

Abstract: Gaussian mixture models are central to classical statistics, widely used in the information sciences, and have a rich mathematical structure. We examine their maximum likelihood estimates through the lens of algebraic statistics. The MLE is not an algebraic function of the data, so there is no notion of ML degree for these models. The critical points of the likelihood function are transcendental, and there is no bound on their number, even for mixtures of two univariate Gaussians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
(33 reference statements)
0
25
0
Order By: Relevance
“…These cubics will be explained in Section 2. For k = 2 we obtain the variety of secant lines, here denoted σ 2 (G 1,6 ). This represents mixtures of two univariate Gaussians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cubics will be explained in Section 2. For k = 2 we obtain the variety of secant lines, here denoted σ 2 (G 1,6 ). This represents mixtures of two univariate Gaussians.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 1. The defining polynomial of σ 2 (G 1,6 ) is a sum of 31154 monomials of degree 39. This polynomial has degrees 25, 33, 32, 23, 17, 12, 9 in m 0 , m 1 , m 2 , m 3 , m 4 , m 5 , m 6 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Minimization of α-divergences allows one to choose a trade-off between mode fitting and support fitting of the minimizer [36]. The minimizer of α-divergences including MLE as a special case has interesting connections with transcendental number theory [37].…”
Section: Bounding the α-Divergencementioning
confidence: 99%
“…While EM remains the most popular method for estimating GMMs, it only guarantees convergence to a stationary point of the likelihood function. On the other hand, various studies have shown that the likelihood function has bad local maxima that can have arbitrarily worse log-likelihood values compared to any of the global maxima [22,25,2]. More importantly, Jin et al [24] proved that with random initialization, the EM algorithm will converge to a bad critical point with high probability.…”
Section: Introductionmentioning
confidence: 99%